Management of intellectual property rights as part of the intangible assets of the enterprise - Maslak, M. V.; Pererva, P. G. (My University, 2022)
The article considers the problems of accounting for intellectual property as part of the intangible assets of an industrial enterprise. It was determined that the problems of development and management of the processes of creation, distribution, use, protection and protection of intellectual property around the world are becoming extremely important and relevant today. It has been proven that the importance and relevance of intellectual property management are determined by two important factors: a) competing enterprises will not be able to fully reproduce the intellectual and innovative technologies used by this enterprise in its production activities; b) intellectual property is of commercial value to the company-owner, as it can be used as part of goods and services. An enterprise may allow third parties to use certain types of its intellectual property, but a system of licenses or other legal restrictions protect this initial exclusive right of the given enterprise.
Управління правами інтелектуальної власності у складі нематеріальних активів підприємства
Keywords: intellectual property; intangible assets; valuation; management; industrial enterprises